This preview shows page 1. Sign up to view the full content.
Unformatted text preview: Follower problem KKT
L(y, λ1, λ2, µ1) = y + λ1 (12 - 2x - y) - λ2 (-4+3x- 2y) + µ1 y
1 - λ1- 2λ2 + µ1 = 0 Complementary Slackness
λ1s1=0 and s1 = 12 - 2x – y
λ2s2=0 and s2 = -4 + 3x - 2y
µ1y = 0 Feasibility conditions
y, s1, s2 ≥0 Positivity
λ1, λ2, µ1 ≥ 0
MIE376 - Mathematical Programming 42 ...
View Full Document
This note was uploaded on 07/10/2011 for the course MIE 376 taught by Professor Daniel during the Spring '11 term at University of Toronto- Toronto.
- Spring '11